Examination of FEMA and the relationship with a community after a disaster - Preussner, Jessi (Kansas State University, 2012)
This report examines the evolution of the Federal Emergency Management Agency. Processes and procedures have evolved overtime and the agency is making strides in improving their reputation. Joplin, Missouri, is used as a case study to determine (1) if there are changes being made in the Federal Emergency Management Agency and (2) outlines the process to receive aid after a natural disaster. Interviews were conducted with officials and members of the public who worked with the Federal Emergency Management Agency after the disaster and their impression of the agency was documented.
Keywords: FEMA; Recovery; Joplin, Missouri; Funding; Area Planning and Development (0341); Public Policy and Social Welfare (0630)